Bullous Henoch-Schönlein Purpura: Case Report - Oliveira, Diana Rita; Maximiano, Cristiana; Leite, Lídia; Abreu, Margarida; Almeida, Filipa Tavares; Ferreira, Olga; Gonçalves, Augusta; Alves, Manuela Costa; Afonso, Ariana (Gazeta Médica, 2021)
INTRODUCTION: Henoch-Schönlein purpura is characterized by palpable purpura associated with abdominal pain, arthralgia or kidney lesion. The bullous variant is rare in children and generally has a good prognosis. CASE REPORT: A 3-year and 8-month-old boy with fever and purpuric lesions that evolved to palpable purpura and bilateral tibiotarsal edema with inability to walk, was diagnosed with Henoch-Schönlein purpura and discharged to the attending physician and pediatric consultation. Due to persistent fever, increased cutaneous lesions (appearance of vesicles and violaceous blisters, some ulcerated lesions), joint edema with inability to walk and stand and abdominal pain, he was reevaluated in the emergency room. Blood analysis with C-reactive protein 29 mg/dL and albumin 3 g/dL, no other alterations. He was hospitalized under amoxicillin/clavulanic acid and methylprednisolone. He presented good clinical evolution, maintaining cicatricial skin lesions and hyperpigmented patches. DISCUSSION: Bullous Henoch-Schönlein purpura is rare in pediatric age and a diagnostic challenge. Corticosteroids may be beneficial in some cases, but more studies are needed to corroborate its use. Most cases have a good prognosis.